Pengaruh Pemberian Tactile Stimulation Masgutova Neurosensorimotor Reflex Integration Dan Perceptual Motor Learning Terhadap Kemampuan Motorik Pada Anak Dengan Developmental Coordination Disorder - Aulia, Rizky; , Dwi Kurniawati, S.ST. Ft., M. Kes; , Isnaini Herawati, S. Fis., M. Sc (2017)
Background: The process of growth and development in children occur simultaneously. Achieving milestones in motor skills, every child shows different movement quality. Some of these children may have difficulties of learning motor skills in daily functional activity or poor performance that referred to as Developmental Coordination Disorder (DCD). DCD affecting about 5%-6% of school-aged children. To stimulate the motoric and sensoric aspect for further developmental rate, we give Tactile Stimulation Masgutova Neurosensorimotor Reflex Integration (MNRI) and Perceptual Motor Learning (PML). Purpose: Knowing the effect of Tactile Stimulation MNRI and PML on motor skills of the children with DCD. Methods: This was a quasi-experimental study with pre and post-test group design. The children in first group received Tactile Stimulation MNRI and the second group received both Tactile Stimulation MNRI ang PML This research included 11 sample of children that the motor skills was measurement with DCD Questionnaire. This research used purposive sampling technique which uses criteria of population: inclusion and exclusion. Result: Wilcoxon test in the first and second group, shown that there is an increase of DCD Questionnare scorring level with p-value≤0,005. From Mann Whitney test, there is significant differences average between two group in pre test and post test with p-value=0,025. The second group had higher motor skills and higher DCD Questionnare scores comparison to the first group. Conclusions: There is effect of Tactile Stimulation MNRI and PML on motor skills of The Children with DCD.